Hegemoni dan kontra hegemoni: memahami perubahan pilihan raya umum Ke-12 - Ghazali Mayudin; Muhamad Nadzri Mohamed Noor (Penerbit UKM, 2008)
The result of to 2008 General Election was a shock to many. For the first time since its establishment, BN failed to gain two third majority in Dewan Rakyat. At the state level, the legistative body in Selangor, Perak, Kedah, Kelantan and Pulau Pinang were also won by the opposition party. For the first time the pattern of voting behaviour was not based on ethnicity or religion. Some Malay candidates were benefited and supported by Indian and Chinese voters. The BN’s failure highlights that majority of voters were capable of swinging their votes. Through this election, the voters clearly demonstrated their capability to select the ‘government by the people’ within the context of a democratic system. This phenomenon was thus widely refered to as ”Political Tsunami”.